Factors Associated with Attention Deficit Hyperactivity Disorder in Children with Frontal Lobe Epilepsy - Kanemura, Hideaki; Sano, Fumikazu; Ohyama, Tetsuo; Sugita, Kanji; Aihara, Masao (Journal of Pediatric Epilepsy, 2017)
The relationship between attention deficit/hyperactivity disorder (ADHD) and frontal lobe epilepsy (FLE) in children is not well understood. Patients with FLE between 6 and 15 years of age were studied. Scores on the ADHD rating scale (ADHD-RS) and Wisconsin card sorting test (WCST) were obtained at baseline. Behavioral changes were evaluated using the ADHD-RS scores at 6, 12, and 24 months after seizure onset. Perseverative errors of Nelson (PEN) scales on WCST were also evaluated at same time periods. The relationships between clinical manifestations and neuropsychological disturbances were analyzed. In 34 patients, the ADHD-RS score at 24 months after onset was most strongly associated with the presence of status epilepticus (SE, p = 0.004, β = 0.490) followed by seizure frequency (p = 0.021, β = 0.382). The increase in ADHD-RS score was most strongly associated with seizure frequency (p < 0.001, β = 0.635). The PEN score on WCST at 24 months was most strongly associated with seizure frequency (p = 0.001, β = 0.724). The increase in PEN score on WCST was most strongly associated with seizure frequency (p = 0.001, β = 0.872). The only clinical factor associated with both the ADHD-RS and the PEN scores on the WCST was seizure frequency. Seizure frequency may be correlated with risk for ADHD in children with FLE.
Keywords: frontal lobe epilepsy; attention deficit/hyperactivity disorder rating scale (ADHD-RS); perseverative errors of Nelson (PEN); seizure frequency